Evaluation on the Corrosion of the Three Ni-Cr Alloys with Different Composition - Srinivasa B. Rao; Ramesh Chowdhary (International Journal of Dentistry)
Dental casting alloys are widely used in contact with oral tissue for many years now. With the development of new dental alloys over the past 15 years, many questions remain unanswered about their biologic safety. Concepts and current issues concerning the response to the biologic effects of dental casting alloys are presented. In this paper, samples of three commercially available nickel-chrome (Ni-cr) casting alloys (Dentaurum, Bego, Sankin) were taken to assess their corrosion behavior, using potentiodynamic polarization method (electrochemical method) with fusayama artificial saliva as an electrolyte medium to check for their biocompatibility. The parameters for corrosion rate and corrosion resistance were obtained from computer-controlled corrosion schematic instrument, namely, potentiostat through corrosion software (power CV). The results obtained were analyzed by classic Tafel analysis. Statistical analysis was done by Student's 𝑡-test and ANOVA test. It was concluded that Dentarum and Bego showed satisfactory corrosive behavior, with exception of Sankin which depicted higher corrosion rate and least resistance to corrosion. Thus, the selection of an alloy should be made on the basis of corrosion resistance and biologic data from dental manufactures.